A STUDY ON ELECTRONIC HUMAN RESOURCE MANAGEMENT (E-HRM) PRACTICES IN APEX FOOTWEAR LIMITED - Jahan, Sabnam (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
This study looks at Apex Footwear Limited’s Electronic Human Resource Management (E-HRM) practices. Human resource services are made available to a wider range of organizational stakeholders, such as HR departments and employees, through web-based technology in E-HRM. The study’s inception followed a comprehensive exploration of the transition from traditional HR to E-HRM, recognizing the integral role of technology in enhancing HR functions, reducing time wastage, and creating a competitive advantage. The primary objective of this study is to investigate E-HRM practices within Apex Footwear Limited. Key goals include scrutinizing E-HRM practices across different departments, gauging employees’ perceptions of E-HRM, assessing its impact on organizational development, identifying implementation obstacles, and providing pertinent recommendations for leveraging E-HRM to enhance organizational performance. The research adopts a descriptive-analytical approach, incorporating both primary and secondary data. A structured questionnaire comprising 11 questions on E-HRM was designed for the study. The study encompasses 80 administrative and management staff members at Apex Footwear Limited, ranging from top-level executives to supervisors, using a convenient sampling approach. The study confirms the positive impact of E-HRM on organizational performance, with employees demonstrating a high level of awareness and satisfaction regarding the system. The study uncovers various challenges in implementing E-HRM, including insufficient financial support, time management issues, and resistance to change. To overcome these challenges, the study recommends aligning E-HRM systems with HR needs, expanding options under E-HR technology, facilitating online training, regular system updates, fostering employee commitment, and adapting to work environment variables. JEL Classification Codes: O32.